Development and Validation of Highly Precise Methods for the Spectrophotometric Determination of Cefpirome in Pharmaceutical Dosage Forms - Hiremath, Basavaraj; Yernale, Nagesh Gunavanthrao; Udayagiri, Mahadev Dhanraj (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: Cefpirome (CFP) in pure and pharmaceutical dosage forms determination by spectrophotometer; two very sensitive techniques have been developed. Materials and Methods: By mixing alkaline β-Naphthol (2-NPL) with diazotized cefpirome drug, we get the pink colour at λmax 544 nm in procedure I. Drug undergoes oxidation by ferric ion followed by complex formation with 2,2’bipyridine (2,2’BPD) to obtain a blood red colour at λmax 520 nm in procedure II. Under ideal conditions, the goal is to maximize the efficiency of procedure I and II. Results: Concentrations of 0.3-3.0 and 0.5-5.0 µg/ml are used in procedures I and II, respectively, where Beer’s rule of molar absorptivity of 1.837 × 105 and 1.470 × 105 is followed. It is possible to calculate three different concentrations of RSD as well as RE (relative error). Conclusion: It was found that the novel procedures may be used to a wide variety of pharmaceutical formulations, and they are simple, consistent, economical, fast and highly reproducible.
Keywords: Accuracy; Cefpirome; Chromogen; Diazotization; Formulation; Oxidation